2021
DOI: 10.3389/ffgc.2021.716582
|View full text |Cite
|
Sign up to set email alerts
|

Insect and Disease Disturbances Correlate With Reduced Carbon Sequestration in Forests of the Contiguous United States

Abstract: Major efforts are underway to harness the carbon sequestration capacity of forests to combat global climate change. However, tree damage and death associated with insect and disease disturbance can reduce this carbon sequestration capacity. We quantified average annual changes in live tree carbon accumulation associated with insect and disease disturbances utilizing the most recent (2001 – 2019) remeasurement data from National Forest Inventory plots in the contiguous United States. Forest plots recently impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Our results further highlight that a significant portion of existing forest carbon offsets face a risk of reversal through wildfire, including all the existing projects in California. Future research and partnerships could build a body of evidence for not only how these improved forest management strategies impact carbon, but also the extent to which they mitigate or exacerbate risk from disturbances such as wildfire 31,38,39 and pest outbreaks 29 . For example, some improved forest management strategies such as thinning reduce fuel loads, but thinning only represented around 10% of credits, whereas no management of projects could increase exposure to risk of catastrophic carbon losses and was the dominant practice in 34% of certified projects (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results further highlight that a significant portion of existing forest carbon offsets face a risk of reversal through wildfire, including all the existing projects in California. Future research and partnerships could build a body of evidence for not only how these improved forest management strategies impact carbon, but also the extent to which they mitigate or exacerbate risk from disturbances such as wildfire 31,38,39 and pest outbreaks 29 . For example, some improved forest management strategies such as thinning reduce fuel loads, but thinning only represented around 10% of credits, whereas no management of projects could increase exposure to risk of catastrophic carbon losses and was the dominant practice in 34% of certified projects (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, wildfires could threaten carbon offsets from forests across the U.S. -not just in the flammable West. Increasing demand for forest based offset credits could also drive the expansion of projects further into fire-prone landscapes, where fuel conditions are further exacerbated by the unpresented drought [27][28][29] . Finally, predictions of future wildfire occurrence and outcomes are inherently uncertain 30 , adding to the uncertainty associated with forest carbon offset permanence.…”
Section: Risk Of Reversal Due To Wildfirementioning
confidence: 99%
“…Major efforts are underway to better understand the effects of disturbances on C sequestration and storage capacities in U.S. forests. For example, Quirion et al (2021) used remeasurement data from national FIA plots and found those plots recently impacted by forest insects sequestered ~69% less C in trees than plots with no recent disturbance. Nationally, they estimated that C sequestration is reduced by ~9.3 Tg C yr -1 in forests that have experienced insect disturbance.…”
Section: Future Wpb Outbreaks and Carbon Lossmentioning
confidence: 99%
“…These include the displacement of native tree species, widespread defoliation, and mortality [10,11]. This reduces the ability of forests to capture and store carbon dioxide, and causes carbon emission release due to wood and canopy decomposition in dead stands [12]. Global warming may promote insect population growth, increase outbreak frequencies, and encourage the geographic expansion of some insect species [13][14][15], violating the global carbon balance.…”
Section: Introductionmentioning
confidence: 99%